A modified silica gel and preparation method thereof

By using composite antistatic agents in silica gel, the π-π interaction between graphene oxide and polyionic liquid and the addition of nano-aluminum powder are solved, and the problems of uneven dispersion and diffusion of antistatic agents are achieved, and efficient and uniform antistatic properties are achieved.

CN119735953APending Publication Date: 2025-04-01DONGGUAN ZHENGNIAN SILICONE FLUORINE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901718.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When traditional silicone is added with antistatic agent, it is difficult to disperse the antistatic agent evenly, and it is easy to diffuse and migrate during use, resulting in a decrease in the antistatic effect with the use time.

Method used

Using composite antistatic agents, graphene oxide is compounded with polyionic liquid with benzene ring to form a π-π interaction, which helps graphene oxide to disperse evenly in the silicone matrix, and enhances the antistatic effect through the addition of nano-aluminum powder.

Benefits of technology

The uniform dispersion of antistatic agents in the silicone system is achieved, the uniformity and durability of the antistatic properties of the product are improved, and the problem of the reduction of the antistatic effect with the use time is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203365430000091
    Figure BDA0005203365430000091
  • Figure BDA0005203365430000101
    Figure BDA0005203365430000101
Patent Text Reader

Abstract

The present invention belongs to the technical field of organic silicon rubber materials. More specifically, it relates to a modified silica gel and a preparation method thereof. The product of the present invention includes a silica gel matrix, and a composite antistatic agent dispersed therein; the composite antistatic agent includes: polyvinyl imidazole, 1-bromo-6-(4-butylazophenyl-4'-oxy) hexane, N,N-dimethylformamide, and tetrahydrofuran are mixed, and then heated in an inert atmosphere for continuous reaction, and the reaction is completed, and tetrahydrofuran is separated and removed, and then bromoacetonitrile is added, and after continuing the heating reaction, it is poured into ether and allowed to stand and precipitate, and then separated to obtain a precipitate, and dried to obtain a dry precursor; the dry precursor and water are mixed and dissolved to obtain a solution A; and bis(trifluoromethanesulfonyl)imide lithium salt and water are mixed and dissolved to obtain a solution B; solution A and solution B are mixed, and graphene oxide is added, heated and stirred to react, filtered, washed and dried, and a composite antistatic agent is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of organic silicon rubber materials, and more specifically, relates to a modified silica gel and a preparation method thereof. Background Art

[0002] Commonly used silicone rubber lacks conductivity, especially the lack of conductivity on the surface. During use, static electricity will accumulate on the surface, resulting in dust absorption. In some fields, such as rubber rollers and foot pads made of silicone.

[0003] In response to the emergence of the above-mentioned technical problems, related technologies began to add antistatic agents to silicone to improve the conductivity of silicone, thus attempting to eliminate static electricity and avoid surface static electricity accumulation; however, in the actual use of the product, it was found that due to the poor compatibility between the antistatic agent and the silicone matrix during the preparation process, the antistatic agent was unevenly dispersed and easily diffused and migrated outward, resulting in uneven antistatic performance or difficulty in lasting.

[0004] Therefore, how to make the added antistatic agent effectively dispersed evenly in the silica gel system so that the antistatic performance of the product is uniform and does not decrease significantly with the extension of the use time is one of the technical problems still faced by technical personnel in this field. Summary of the invention

[0005] The technical problem to be solved by the present invention is that, in the process of adding antistatic agent to traditional silica gel, the antistatic agent is difficult to be evenly dispersed in the system, and is also prone to diffusion and migration during use, resulting in the antistatic effect of the product being continuously reduced during use. Based on the above difficulties, the present invention provides a modified silica gel and a preparation method thereof.

[0006] The purpose of the present invention is to provide a modified silica gel.

[0007] Another object of the present invention is to provide a method for preparing modified silica gel.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] A modified silica gel, comprising a silica gel matrix and a composite antistatic agent dispersed therein;

[0010] Wherein, the dosage of the composite antistatic agent is 10-15% of the mass of the silica gel matrix;

[0011] The compounding process of the composite antistatic agent comprises:

[0012] By weight, 40-50 parts of polyvinylimidazole, 50-60 parts of 1-bromo-6-(4-butylazophenyl-4'-oxyl)hexane, 800-1000 parts of N,N-dimethylformamide, 300-400 parts of tetrahydrofuran, and 110-120 parts of bromoacetonitrile;

[0013] Polyvinyl imidazole, 1-bromo-6-(4-butylazophenyl-4'-oxy)hexane, N,N-dimethylformamide and tetrahydrofuran are mixed, and heated continuously in an inert atmosphere for reaction. After the reaction is completed, the tetrahydrofuran is separated and removed, and bromoacetonitrile is added, and the mixture is heated and reacted continuously. The mixture is poured into ether and allowed to stand for precipitation, and the precipitate is separated and dried to obtain a dry precursor;

[0014] Weigh a dry precursor and bis(trifluoromethanesulfonyl)imide lithium salt at a mass ratio of 1:1-1.2, mix and dissolve the dry precursor and water to obtain solution A; and mix and dissolve bis(trifluoromethanesulfonyl)imide lithium salt and water to obtain solution B;

[0015] Solution A and solution B are mixed, and graphene oxide in an amount of 0.2-0.3 times the mass of the dry precursor is added, and after ultrasonic dispersion, heating and stirring are performed for reaction. After the reaction is completed, suction filtration, washing and drying are performed to obtain a composite antistatic agent.

[0016] The above technical solution uses graphene oxide and polyionic liquid with benzene ring as antistatic agent for use in silica gel, wherein the polyionic liquid itself has a good antistatic effect. However, the inventors found that if a single ionic liquid is added, it is easy to disperse in the silica gel matrix in the early stage of the preparation process, but with the long-term use of the product, especially when encountering long-term erosion in a humid and hot air environment, it is easy to diffuse and migrate, thereby causing the antistatic effect of the product to decrease with the extension of the service life;

[0017] In addition, although graphene oxide is added to the silica gel matrix and can also be used alone as an antistatic agent, the inventors found that the density of graphene oxide is relatively small and it is difficult to disperse evenly in the silica gel matrix during the silica gel processing. Therefore, the antistatic uniformity of the product is insufficient.

[0018] By compounding the above two components in advance, during the compounding process, with the help of the benzene ring of the ionic liquid, a π-π interaction can be formed with the conjugated region of graphene oxide, so that the two can be effectively compounded. In the early preparation process, the presence of the polyionic liquid can assist the effective dispersion of graphene oxide in the silica gel matrix. Later, with the use of the product, the diffusion or migration of the polyionic liquid becomes extremely difficult due to the restraining effect of graphene oxide. In addition, the layered structure of graphene oxide can also effectively cut off the diffusion path of air and water vapor during the wet heat aging process. Therefore, the product obtains a uniform antistatic effect in the early preparation process, and this performance is also effectively maintained during long-term use.

[0019] Furthermore, the D50 of the graphene oxide is 95-100 nm; and the particle size distribution range of the graphene oxide is 80-120 nm.

[0020] The use of graphene oxide with a narrow particle size distribution range makes the particle size of graphene oxide more concentrated, so that a more homogeneous composite material can be formed during the compounding process. When added to the product, it is easy to form an antistatic effect with uniform performance in different regions.

[0021] Furthermore, anionic surfactants are dispersed between the layers of the graphene oxide;

[0022] The anionic surfactant is selected from any one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium linear alkylbenzene sulfonate, sodium α-olefin sulfonate, succinate ester sulfonate, sodium lignin sulfonate, α-sulfo fatty acid methyl ester (mono) sodium salt, sodium lauryl sulfate, and sodium fatty alcohol polyoxyethylene ether sulfate.

[0023] By dispersing anionic surfactants between the graphene oxide layers, the distance between the graphene oxide layers can be widened, thereby facilitating the compounding process so that the benzene rings in the molecular structure of the polyionic liquid can more easily form strong interactions with the conjugated regions of the graphene oxide.

[0024] Furthermore, the interlayer of the graphene oxide further includes nano-aluminum powder, and the D50 of the nano-aluminum powder is 0.1-0.15 times the D50 of the graphene oxide.

[0025] By further embedding a certain amount of nano-aluminum powder between the layers of graphene oxide, the antistatic effect of the product is further improved. This improvement mainly comes from the dispersion of nano-aluminum powder between the graphene oxide layers after the interlayer spacing is widened. In this way, two adjacent layers of graphene oxide sheets can be connected to form a three-dimensional conductive path, thereby avoiding the decrease in the conductivity of graphene oxide itself due to the widening of its interlayer spacing.

[0026] Furthermore, the composite process of the composite antistatic agent includes: reacting the nano aluminum powder, anionic surfactant and graphene oxide to obtain pretreated graphene oxide;

[0027] The specific preparation steps of the pretreated graphene oxide include:

[0028] The graphene oxide and nano-aluminum powder are dispersed in deionized water, and an anionic surfactant is added, and then ultrasonic dispersion is performed for 40-60 minutes at a temperature of 40-50° C. and an ultrasonic frequency of 120-140 kHz, and then the filter cake is collected by suction filtration and then vacuum freeze-dried to obtain pretreated graphene oxide;

[0029] Under the action of ultrasonic treatment, the interlayer spacing of graphene oxide was effectively widened by the action of anionic surfactants, and some layers even peeled off. In the subsequent filtration process, the nano-aluminum powder was smoothly embedded in the interlayer of graphene oxide as the layers accumulated.

[0030] Wherein, the dosage of the nano aluminum powder is 8-10% of the mass of the graphene oxide.

[0031] A method for preparing modified silica gel, the specific preparation steps comprising:

[0032] 100-120 parts by weight of alkoxy-terminated polydimethylsiloxane, 0.3-0.5 parts of vinyltrimethoxysilane, 0.4-0.6 parts of methyltrimethoxysilane, and 0.03-0.05 parts of an organic tin catalyst are mixed to form a silica gel matrix;

[0033] and adding a composite antistatic agent to the silica gel matrix;

[0034] After heating and kneading evenly, the mixture is cooled to obtain modified silica gel.

[0035] Furthermore, the organic tin catalyst is selected from any one of tin octoate, dioctyltin, dioctyltin mercaptan, and dibutyltin diacetate.

[0036] Furthermore, the alkoxy-terminated polydimethylsiloxane is composed of 1# alkoxy-terminated polydimethylsiloxane and 2# alkoxy-terminated polydimethylsiloxane of equal mass;

[0037] The viscosity of the 1# alkoxy-terminated polydimethylsiloxane is greater than the viscosity of the 2# alkoxy-terminated polydimethylsiloxane;

[0038] The viscosity is the viscosity at a temperature of 25°C, and the viscosity of the 1# alkoxy-terminated polydimethylsiloxane is 20000-21000 mPa·s; the viscosity of the 2# alkoxy-terminated polydimethylsiloxane is 18000-19000 mPa·s;

[0039] Furthermore, when preparing the modified silica gel, the steps include:

[0040] First, heat and mix 1# alkoxy-terminated polydimethylsiloxane and composite antistatic agent evenly, then add 2# alkoxy-terminated polydimethylsiloxane, vinyltrimethoxysilane, methyltrimethoxysilane and organic tin catalyst, continue to mix evenly, and cool to obtain modified silica gel.

[0041] The above technical solution adopts two organosiloxanes of different viscosities as raw materials, and when preparing silica gel, the siloxane with higher viscosity is first heated and mixed with the composite antistatic agent. During this process, the higher viscosity can provide higher shear force to the graphene oxide, which is conducive to the effective dissociation and dispersion of the antistatic agent after compounding; this is mainly because, during the compounding process of graphene oxide, its layers are easily re-stacked, and under the action of shear force, slip occurs between the layers, thereby exposing the internal polyionic liquid, or causing the soft agglomerated parts to be dissociated, and finally achieving a uniform dispersion effect. DETAILED DESCRIPTION

[0042] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0043] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0044] Example 1

[0045] Pretreatment of graphene oxide:

[0046] Graphene oxide and nano-aluminum powder with a mass percentage of 8% of the graphene oxide are mixed, and then poured into deionized water, wherein the amount of deionized water is 12 times the mass of the graphene oxide; an anionic surfactant with a mass percentage of 1% of the graphene oxide is added, and then ultrasonic dispersion is performed for 40 minutes at a temperature of 40° C. and an ultrasonic frequency of 120 kHz, and then the filter cake is collected by suction filtration and vacuum freeze-dried to obtain pretreated graphene oxide;

[0047] The D50 of the graphene oxide is 95 nm; and the particle size distribution range of the graphene oxide is 80-120 nm;

[0048] The D50 of the nano aluminum powder is 0.1 times the D50 of the graphene oxide;

[0049] The anionic surfactant is selected from: sodium lauryl sulfate;

[0050] Preparation of composite antistatic agent:

[0051] By weight, take 40 parts of polyvinylimidazole, 50 parts of 1-bromo-6-(4-butylazophenyl-4'-oxy)hexane, 800 parts of N,N-dimethylformamide, 300 parts of tetrahydrofuran, and 110 parts of bromoacetonitrile;

[0052] After polyvinyl imidazole, 1-bromo-6-(4-butylazophenyl-4'-oxy)hexane, N,N-dimethylformamide and tetrahydrofuran are mixed, the mixture is heated and reacted for 48 hours in an inert atmosphere at a temperature of 80°C and a stirring speed of 200 r / min. After the reaction is completed, the tetrahydrofuran is separated and removed, and bromoacetonitrile is added. The mixture is heated and reacted for 48 hours at a temperature of 80°C and a stirring speed of 200 r / min. The mixture is then poured into ether and allowed to stand for 12 hours to precipitate. The precipitate is then separated by centrifugation and dried to obtain a dry precursor.

[0053] The dry precursor and the lithium salt of bis(trifluoromethanesulfonyl)imide are weighed at a mass ratio of 1:1, and the dry precursor and water are mixed and dissolved to obtain a solution A, wherein the amount of water used is 8 times the mass of the dry precursor; and the lithium salt of bis(trifluoromethanesulfonyl)imide and water are mixed and dissolved to obtain a solution B, wherein the amount of water used is 8 times the mass of the lithium salt of bis(trifluoromethanesulfonyl)imide;

[0054] Solution A and solution B were mixed, and 0.2 times the mass of the dry precursor graphene oxide was added, and after ultrasonic dispersion, the mixture was heated and stirred at a temperature of 75°C and a rotation speed of 300 r / min for 3 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain a composite antistatic agent.

[0055] In parts by weight, 100 parts of alkoxy-terminated polydimethylsiloxane, 0.3 parts of vinyltrimethoxysilane, 0.4 parts of methyltrimethoxysilane, and 0.03 parts of an organic tin catalyst are taken, and the total weight of the above components is used as the weight basis of the silica gel matrix;

[0056] Wherein, the alkoxy-terminated polydimethylsiloxane is composed of 1# alkoxy-terminated polydimethylsiloxane and 2# alkoxy-terminated polydimethylsiloxane of equal mass;

[0057] The viscosity of the 1# alkoxy-terminated polydimethylsiloxane is greater than the viscosity of the 2# alkoxy-terminated polydimethylsiloxane;

[0058] The viscosity is the viscosity at a temperature of 25°C, and the viscosity of the 1# alkoxy-terminated polydimethylsiloxane is 20000 mPa·s; the viscosity of the 2# alkoxy-terminated polydimethylsiloxane is 18000 mPa·s;

[0059] and adding a composite antistatic agent to the silica gel matrix; the amount of the composite antistatic agent is 10% of the mass of the silica gel matrix;

[0060] First, 1# alkoxy-terminated polydimethylsiloxane and composite antistatic agent are heated and mixed for 30 minutes at a temperature of 45°C and a rotation speed of 80r / min, and then 2# alkoxy-terminated polydimethylsiloxane, vinyl trimethoxysilane, methyl trimethoxysilane, and organic tin catalyst are added, and the mixture is heated and mixed for 30 minutes at a temperature of 45°C and a rotation speed of 80r / min, and then cooled to obtain modified silica gel;

[0061] The organotin catalyst is selected from tin octoate.

[0062] Example 2

[0063] Pretreatment of graphene oxide:

[0064] Graphene oxide and nano-aluminum powder with a mass percentage of 9% of the graphene oxide are mixed, and then poured into deionized water, wherein the amount of deionized water is 14 times the mass of the graphene oxide; an anionic surfactant with a mass percentage of 1.5% of the graphene oxide is added, and then ultrasonic dispersion is performed for 50 minutes at a temperature of 45° C. and an ultrasonic frequency of 130 kHz, and then the filter cake is collected by suction filtration and vacuum freeze-dried to obtain pretreated graphene oxide;

[0065] The D50 of the graphene oxide is 98 nm; and the particle size distribution range of the graphene oxide is 80-120 nm;

[0066] The D50 of the nano aluminum powder is 0.12 times the D50 of the graphene oxide;

[0067] The anionic surfactant is selected from: sodium dodecylbenzene sulfonate;

[0068] Preparation of composite antistatic agent:

[0069] By weight, 46 parts of polyvinylimidazole, 55 parts of 1-bromo-6-(4-butylazophenyl-4'-oxy)hexane, 900 parts of N,N-dimethylformamide, 360 parts of tetrahydrofuran, and 115 parts of bromoacetonitrile were taken;

[0070] After polyvinyl imidazole, 1-bromo-6-(4-butylazophenyl-4'-oxy)hexane, N,N-dimethylformamide and tetrahydrofuran are mixed, the mixture is heated and reacted for 52 hours in an inert atmosphere at a temperature of 82°C and a stirring speed of 200 r / min. After the reaction is completed, the tetrahydrofuran is separated and removed, and bromoacetonitrile is added. The mixture is heated and reacted for 52 hours at a temperature of 82°C and a stirring speed of 200 r / min. The mixture is then poured into ether and allowed to stand for 12 hours to precipitate. The precipitate is then separated by centrifugation and dried to obtain a dry precursor.

[0071] The dry precursor and the lithium salt of bis(trifluoromethanesulfonyl)imide are weighed at a mass ratio of 1:1.1, and the dry precursor and water are mixed and dissolved to obtain a solution A, wherein the amount of water used is 8 times the mass of the dry precursor; and the lithium salt of bis(trifluoromethanesulfonyl)imide and water are mixed and dissolved to obtain a solution B, wherein the amount of water used is 8 times the mass of the lithium salt of bis(trifluoromethanesulfonyl)imide;

[0072] Solution A and solution B were mixed, and 0.24 times the mass of the dry precursor graphene oxide was added, and after ultrasonic dispersion, the mixture was heated and stirred at a temperature of 78° C. and a rotation speed of 300 r / min for 4 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain a composite antistatic agent.

[0073] In parts by weight, 110 parts of alkoxy-terminated polydimethylsiloxane, 0.4 parts of vinyltrimethoxysilane, 0.5 parts of methyltrimethoxysilane, and 0.04 parts of an organic tin catalyst are taken, and the total weight of the above components is used as the weight basis of the silica gel matrix;

[0074] Wherein, the alkoxy-terminated polydimethylsiloxane is composed of 1# alkoxy-terminated polydimethylsiloxane and 2# alkoxy-terminated polydimethylsiloxane of equal mass;

[0075] The viscosity of the 1# alkoxy-terminated polydimethylsiloxane is greater than the viscosity of the 2# alkoxy-terminated polydimethylsiloxane;

[0076] The viscosity is the viscosity at a temperature of 25°C, and the viscosity of the 1# alkoxy-terminated polydimethylsiloxane is 20000 mPa·s; the viscosity of the 2# alkoxy-terminated polydimethylsiloxane is 19000 mPa·s;

[0077] and adding a composite antistatic agent to the silica gel matrix; the amount of the composite antistatic agent is 12% of the mass of the silica gel matrix;

[0078] First, 1# alkoxy-terminated polydimethylsiloxane and composite antistatic agent are heated and mixed for 30 minutes at a temperature of 48°C and a rotation speed of 80r / min, and then 2# alkoxy-terminated polydimethylsiloxane, vinyl trimethoxysilane, methyl trimethoxysilane and organic tin catalyst are added, and the mixture is heated and mixed for 30 minutes at a temperature of 48°C and a rotation speed of 80r / min, and then cooled to obtain modified silica gel;

[0079] The organotin catalyst is selected from dioctyltin.

[0080] Example 3

[0081] Pretreatment of graphene oxide:

[0082] Graphene oxide and nano-aluminum powder with a mass content of 10% of the mass of graphene oxide are mixed, and then poured into deionized water, wherein the amount of deionized water used is 15 times the mass of graphene oxide; an anionic surfactant with a mass content of 2% of the mass of graphene oxide is then added, and then ultrasonic dispersion is performed for 60 minutes at a temperature of 50° C. and an ultrasonic frequency of 140 kHz, and then the filter cake is collected by suction filtration and then freeze-dried in vacuum to obtain pretreated graphene oxide;

[0083] The D50 of the graphene oxide is 100 nm; and the particle size distribution range of the graphene oxide is 80-120 nm;

[0084] The D50 of the nano aluminum powder is 0.15 times the D50 of the graphene oxide;

[0085] The anionic surfactant is selected from: sodium lignin sulfonate;

[0086] Preparation of composite antistatic agent:

[0087] By weight, take 50 parts of polyvinylimidazole, 60 parts of 1-bromo-6-(4-butylazophenyl-4'-oxy)hexane, 1000 parts of N,N-dimethylformamide, 400 parts of tetrahydrofuran, and 120 parts of bromoacetonitrile;

[0088] After polyvinyl imidazole, 1-bromo-6-(4-butylazophenyl-4'-oxy)hexane, N,N-dimethylformamide and tetrahydrofuran are mixed, the mixture is heated and reacted for 56 hours in an inert atmosphere at a temperature of 85°C and a stirring speed of 200 r / min. After the reaction is completed, the tetrahydrofuran is separated and removed, and bromoacetonitrile is added. The mixture is heated and reacted for 56 hours at a temperature of 85°C and a stirring speed of 200 r / min. The mixture is then poured into ether and allowed to stand for 12 hours to precipitate. The precipitate is then separated by centrifugation and dried to obtain a dry precursor.

[0089] The dry precursor and the lithium salt of bis(trifluoromethanesulfonyl)imide are weighed at a mass ratio of 1:1.2, and the dry precursor and water are mixed and dissolved to obtain a solution A, wherein the amount of water used is 8 times the mass of the dry precursor; and the lithium salt of bis(trifluoromethanesulfonyl)imide and water are mixed and dissolved to obtain a solution B, wherein the amount of water used is 8 times the mass of the lithium salt of bis(trifluoromethanesulfonyl)imide;

[0090] Solution A and solution B are mixed, and 0.3 times the mass of the dry precursor graphene oxide is added, and after ultrasonic dispersion, the mixture is heated and stirred at a temperature of 80° C. and a rotation speed of 300 r / min for a reaction of 5 h. After the reaction is completed, the mixture is filtered, washed and dried to obtain a composite antistatic agent;

[0091] In parts by weight, 120 parts of alkoxy-terminated polydimethylsiloxane, 0.5 parts of vinyltrimethoxysilane, 0.6 parts of methyltrimethoxysilane, and 0.05 parts of an organic tin catalyst are taken, and the total weight of the above components is used as the weight basis of the silica gel matrix;

[0092] Wherein, the alkoxy-terminated polydimethylsiloxane is composed of 1# alkoxy-terminated polydimethylsiloxane and 2# alkoxy-terminated polydimethylsiloxane of equal mass;

[0093] The viscosity of the 1# alkoxy-terminated polydimethylsiloxane is greater than the viscosity of the 2# alkoxy-terminated polydimethylsiloxane;

[0094] The viscosity is the viscosity at a temperature of 25°C, and the viscosity of the 1# alkoxy-terminated polydimethylsiloxane is 21000 mPa·s; the viscosity of the 2# alkoxy-terminated polydimethylsiloxane is 18000 mPa·s;

[0095] and adding a composite antistatic agent to the silica gel matrix; the amount of the composite antistatic agent is 15% of the mass of the silica gel matrix;

[0096] First, 1# alkoxy-terminated polydimethylsiloxane and composite antistatic agent are heated and mixed for 30 minutes at a temperature of 50°C and a rotation speed of 80r / min, and then 2# alkoxy-terminated polydimethylsiloxane, vinyl trimethoxysilane, methyl trimethoxysilane, and organic tin catalyst are added, and the mixture is heated and mixed for 30 minutes at a temperature of 50°C and a rotation speed of 80r / min, and then cooled to obtain modified silica gel;

[0097] The organotin catalyst is selected from dibutyltin diacetate.

[0098] Example 4

[0099] The difference between this embodiment and embodiment 1 is that the viscosity of 1# alkoxy-terminated polydimethylsiloxane is the same as the viscosity of 2# alkoxy-terminated polydimethylsiloxane, and both are 18000 mPa·s, and the other conditions remain unchanged; thus, in the final mixing process, the uniformity decreases compared to embodiment 1.

[0100] Example 5

[0101] The present embodiment is different from the embodiment 1 in that no nano aluminum powder is added, and other conditions remain unchanged; due to the lack of nano aluminum powder, the antistatic effect of the product is slightly reduced.

[0102] Comparative Example 1

[0103] The difference between this comparative example and Example 1 is that no pretreated graphene oxide is added, and the other conditions remain unchanged.

[0104] Comparative Example 2

[0105] The difference between this comparative example and Example 1 is that the composite antistatic agent of equal quality is replaced by pretreated graphene oxide, and the other conditions remain unchanged.

[0106] The performance tests were performed on the products obtained in the above embodiments and comparative examples. The specific test methods and test results are as follows:

[0107] Referring to GB / T 2439-2001, the resistivity of the products obtained in the above embodiments and comparative examples was tested;

[0108] During the test, 10 sets of parallel samples were set for each sample to obtain the average value 1 and the range between the maximum and minimum values;

[0109] The samples were placed in an aging test chamber at a temperature of 40°C and a relative humidity of 85% for 28 days and then tested again to obtain an average value of 2.

[0110] The relevant test results are shown in Table 1;

[0111] Table 1: Product performance test results

[0112]

[0113]

[0114] It can be seen from the test results in Table 1 that the product obtained by the present invention can effectively take into account the uniformity of the antistatic ability and the aging resistance of the product.

[0115] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A modified silica gel, characterized in that: It includes a silica gel matrix and a composite antistatic agent dispersed therein; Wherein, the dosage of the composite antistatic agent is 10-15% of the mass of the silica gel matrix; The compounding process of the composite antistatic agent comprises: By weight, 40-50 parts of polyvinylimidazole, 50-60 parts of 1-bromo-6-(4-butylazophenyl-4'-oxyl)hexane, 800-1000 parts of N,N-dimethylformamide, 300-400 parts of tetrahydrofuran, and 110-120 parts of bromoacetonitrile; Polyvinyl imidazole, 1-bromo-6-(4-butylazophenyl-4'-oxy)hexane, N,N-dimethylformamide and tetrahydrofuran are mixed, and heated continuously in an inert atmosphere for reaction. After the reaction is completed, the tetrahydrofuran is separated and removed, and bromoacetonitrile is added, and the mixture is heated and reacted continuously. The mixture is poured into ether and allowed to stand for precipitation, and the precipitate is separated and dried to obtain a dry precursor; Weigh a dry precursor and bis(trifluoromethanesulfonyl)imide lithium salt at a mass ratio of 1:1-1.2, mix and dissolve the dry precursor and water to obtain solution A; and mix and dissolve bis(trifluoromethanesulfonyl)imide lithium salt and water to obtain solution B; Solution A and solution B are mixed, and graphene oxide in an amount of 0.2-0.3 times the mass of the dry precursor is added, and after ultrasonic dispersion, heating and stirring are performed for reaction. After the reaction is completed, suction filtration, washing and drying are performed to obtain a composite antistatic agent.

2. A modified silica gel according to claim 1, characterized in that: The D50 of the graphene oxide is 95-100 nm; and the particle size distribution range of the graphene oxide is 80-120 nm.

3. A modified silica gel according to claim 2, characterized in that: Anionic surfactants are dispersed between the layers of the graphene oxide; The anionic surfactant is selected from any one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium linear alkylbenzene sulfonate, sodium α-olefin sulfonate, succinate ester sulfonate, sodium lignin sulfonate, α-sulfo fatty acid methyl ester (mono) sodium salt, sodium lauryl sulfate, and sodium fatty alcohol polyoxyethylene ether sulfate.

4. A modified silica gel according to claim 3, characterized in that: The graphene oxide also includes nano-aluminum powder between the layers, and the D50 of the nano-aluminum powder is 0.1-0.15 times the D50 of the graphene oxide.

5. A modified silica gel according to claim 4, characterized in that: The composite process of the composite antistatic agent includes: reacting the nano aluminum powder, anionic surfactant and graphene oxide to obtain pretreated graphene oxide; The specific preparation steps of the pretreated graphene oxide include: The graphene oxide and nano-aluminum powder are dispersed in deionized water, and an anionic surfactant is added, and then ultrasonic dispersion is performed for 40-60 minutes at a temperature of 40-50° C. and an ultrasonic frequency of 120-140 kHz, and then the filter cake is collected by suction filtration and then vacuum freeze-dried to obtain pretreated graphene oxide; Wherein, the dosage of the nano aluminum powder is 8-10% of the mass of the graphene oxide.

6. A method for preparing the modified silica gel according to any one of claims 1 to 5, characterized in that: The specific preparation steps include: 100-120 parts by weight of alkoxy-terminated polydimethylsiloxane, 0.3-0.5 parts of vinyltrimethoxysilane, 0.4-0.6 parts of methyltrimethoxysilane, and 0.03-0.05 parts of an organic tin catalyst are mixed to form a silica gel matrix; and adding a composite antistatic agent to the silica gel matrix; After heating and kneading evenly, the mixture is cooled to obtain modified silica gel.

7. The method for preparing modified silica gel according to claim 6, characterized in that: The organic tin catalyst is selected from any one of tin octoate, dioctyltin, dioctyltin mercaptan, and dibutyltin diacetate.

8. The method for preparing modified silica gel according to claim 6, characterized in that: The alkoxy-terminated polydimethylsiloxane is composed of 1# alkoxy-terminated polydimethylsiloxane and 2# alkoxy-terminated polydimethylsiloxane of equal mass; The viscosity of the 1# alkoxy-terminated polydimethylsiloxane is greater than the viscosity of the 2# alkoxy-terminated polydimethylsiloxane; The viscosity is the viscosity at a temperature of 25°C, and the viscosity of the 1# alkoxy-terminated polydimethylsiloxane is 20000-21000 mPa·s; the viscosity of the 2# alkoxy-terminated polydimethylsiloxane is 18000-19000 mPa·s; Furthermore, when preparing the modified silica gel, the steps include: First, heat and mix 1# alkoxy-terminated polydimethylsiloxane and composite antistatic agent evenly, then add 2# alkoxy-terminated polydimethylsiloxane, vinyltrimethoxysilane, methyltrimethoxysilane and organic tin catalyst, continue to mix evenly, and cool to obtain modified silica gel.